A NOVEL PHENOLIC DERIVATIVE FROM THE AERIAL PARTS OF INDIGOFERRA ARRECTA HOCHST. EX A.RICH (PAPILIONOICEAE) - Adejoke. S. A; Hassan H. S.; Musa A. M.; Atiku I.; Jimoh A. A.; Moses K. Langat; Yusuf A. J. (Zagazig Journal of Pharmaceutical Sciences)
Indigofera arrecta (Papilionoideae) is a widely recognized medicinal plant traditionally used in various cultures for the treatment of ailments such as epilepsy, snakebites, and jaundice. The therapeutic potential of this plant is attributed to its rich phytochemical composition, which includes bioactive secondary metabolites with significant pharmacological properties. In this study, we report the isolation and structural characterization of a novel phenolic compound,4-[3'-(2’-hexyloxy-ethoxy)-1'-hydroxy-2'-methoxypropyl]-2-methoxyphenol, from the aerial parts of I. arrecta. The compound was purified using chromatographic techniques, and its chemical structure was elucidated through comprehensive spectroscopic analyses, including ultraviolet (UV), infrared (IR), and one-dimensional (1D) and two-dimensional (2D) nuclear magnetic resonance (NMR) spectroscopy. To the best of our knowledge, this is the first report of this compound being identified from a natural source. Its structural features indicate a high likelihood of possessing significant pharmacological activities. Given its phenolic nature, it is hypothesized that this compound exhibits antioxidant, anti-inflammatory, and antimicrobial properties, making it a promising candidate for further biological evaluation and potential drug development. These findings contribute to the growing body of research on I.arrecta and its bioactive constituents, reinforcing the plant’s traditional medicinal use and expanding the scope of its pharmacological potential. Further studies, including in vitro and in vivo biological assays, are warranted to confirm its therapeutic efficacy and explore its mechanism of action. This research highlights the importance of natural product chemistry in the discovery of novel bioactive compounds with potential pharmaceutical applications.